Regulatory compliance among over-the-counter medicine sellers facilities within the Upper East Region of Ghana - Benjamin Kwarteng Frempong; Anthony Amalba; Nina Donkor; Kwadwo Owusu Akuffo (Taylor & Francis Group, 2021)
Background Easy access to medicines provided by private medicine retailing facilities including that of over-the-counter medicine retailers, have gained prominence in sub-Saharan Africa. Although over-the-counter medicine-sellers (OTCMS) facilities play an indispensable role in healthcare delivery, there is inadequate information about their regulatory environment and whether their operations conform to regulatory provisions. Hence, this study sought to investigate the characteristics and predictors of regulatory practices among over-the-counter medicine sellers in Ghana. Methods This was a cross-sectional study involving participants from 208 OTCMS facilities in eight (8) municipalities and districts (MDA's) of the Upper East Region of Ghana. An initial census of facilities in the region was conducted between May and August 2016 and a follow-up conducted between December 2016 and March 2017. This ensured the identification and location of all OTCMS facilities within the selected MDA's for study planning and data collection. The main outcome variable was regulatory compliance which is a composite of three indicators for regulatory practices (retention of medicine supplier's invoices and receipts on-premises), licensing and registration requirements (appropriate signage), and equipment and material requirements (availability of reference material). Regulatory compliance was assessed using bivariate and multivariate logistic regression analyses. Results In this survey, 21.5%, 38.2%, and 23.1% of the facilities surveyed had a good state of repair, had the owner of the facility available on the premises, and had received regulatory visit(s) in less than 12 months, respectively. Only 29.2% of facilities were regulatory compliant. After statistical adjustment, OTCMS facility location (compared with Rural: Urban, AOR = 4.2, 95% CI 1.74-10.17, p = 0.001) and staff trained in less than 1 year (AOR = 2.78, 95% CI 1.02-7.62, p = 0.046) were significantly associated with regulatory compliance. Conclusions Regulatory compliance was low in the Upper East Region of Ghana, particularly across rural locations, where most of the facilities failed to meet the laid down provisions of the Pharmacy Council regarding practice, staff and premises requirements. This could be attributed to the fact that these areas are poorly resourced. Policymakers are been called on to put in place pragmatic measures in relation to OTCMS facility's location and regulatory requirements to address the inequities in compliance.